2011
DOI: 10.1016/j.jacc.2011.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Monomorphic Ventricular Tachycardia and Mediastinal Adenopathy Due to Granulomatous Infiltration in Patients With Preserved Ventricular Function

Abstract: A subset of patients with SMVT with preserved ventricular function has a syndrome of arrhythmogenic myocarditis with granulomatous mediastinal adenopathy due to myocardial tuberculosis or cardiac sarcoidosis. This entity is optimally managed with a combination of disease-specific therapy and antiarrhythmic measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 9 publications
0
40
0
Order By: Relevance
“…A recent study with FDG-PET in patients with sustained monomorphic ventricular tachycardia and sarcoidosis or tuberculosis demonstrated that myocardial inflammation may cause life-threatening ventricular arrhythmias and abnormal electroanatomic mapping findings even in the absence of scar at cardiac magnetic resonance and in the presence of normal ventricular dimensions and function. 26 Moreover, it has been demonstrated that continuing myocardial damage can persist even in the absence of overt inflammation, for example, through the release of viral proteases capable of cleaving cytoskeletal dystrophin. 27,28 The 2006 European Society of Cardiology/American College of Cardiology/American Heart Association guidelines on ventricular arrhythmias and sudden cardiac death 10 recommend drug therapy for life-threatening ventricular arrhythmias in myocarditis.…”
Section: Ventricular Arrhythmias In Myocarditismentioning
confidence: 99%
“…A recent study with FDG-PET in patients with sustained monomorphic ventricular tachycardia and sarcoidosis or tuberculosis demonstrated that myocardial inflammation may cause life-threatening ventricular arrhythmias and abnormal electroanatomic mapping findings even in the absence of scar at cardiac magnetic resonance and in the presence of normal ventricular dimensions and function. 26 Moreover, it has been demonstrated that continuing myocardial damage can persist even in the absence of overt inflammation, for example, through the release of viral proteases capable of cleaving cytoskeletal dystrophin. 27,28 The 2006 European Society of Cardiology/American College of Cardiology/American Heart Association guidelines on ventricular arrhythmias and sudden cardiac death 10 recommend drug therapy for life-threatening ventricular arrhythmias in myocarditis.…”
Section: Ventricular Arrhythmias In Myocarditismentioning
confidence: 99%
“…Recurrence was significantly reduced from “6.5 VTs/patient-year to 0.6 VTs/patient-year” by introducing disease-specific therapy [6]. In both our patients, treatment consisted of antiarrhythmic drugs, quadruple anti-tuberculous medication and the implantation of an ICD, with successful outcome.…”
Section: Discussionmentioning
confidence: 78%
“…Significant lymphadenopathy became apparent, raising the possibility of TB or sarcoidosis. In select cases endomyocardial biopsies were performed to seek a histopathological diagnosis and tissue for TB culture [6]. The importance of searching for lymphadenopathy is highlighted in this study whereby even in those patients without cardiac inflammation on CMR, mediastinal nodes were found on PET.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Granulomatous myocardial infiltration or fibrosis enhances abnormal automaticity and re-entrant substrate [107]. These arrhythmias can be observed during CS without cardiac dysfunction [108]. Ventricular ectopic beats are frequent (37% of cases).…”
Section: Electrocardiogrammentioning
confidence: 99%